ORAL MUCOSITIS MANAGEMENT IN A PEDIATRIC PATIENT WITH ACUTE LYMPHOBLASTIC LEUKEMIA: CASE REPORT - Nydia Hanan (Universitas Baiturrahmah, 2022)
Introduction: Acute leukemia is a primary malignancy in the bone marrow, in children constituting 35% of childhood cancers. Eighty percent are Acute Lymphocytic Leukemia (ALL) and 20% are Acute Myeloid Leukemia (AML). In Indonesia, there are currently around 80,000 children under the age of 15 years. Mucositis, oral infections, taste dysfunction, xerostomia, and bleeding are recognized as common acute sequels with risks for severe pain, malnutrition, and potential source of systemic infections. The purpose of this article is to report the management of mucositis in a patient with Acute Lymphoblastic Leukemia. Case and Management: A 5 years old boy consulted from Pediatrician in Abdoel Wahab Sjahranie General Hospital to a Pediatric Dentist in the same hospital with the chief complaint of severe gingivitis, bleeding on gingival mucosa, ulcer, and mucositis on lips. Because the general conditions of the patient decreased, the supportive therapies were instructed to maintain oral hygiene by rinsing and cleaning intra-oral with sterile gauze with sterile or cold water and chlorhexidine gluconate 0,20% periodically, brushing teeth with soft bristles, applying oxygel, and soft diets with high in carbohydrate and protein. Conclusion: The risks of mucositis in children are higher compared with adults due to the uncooperative behavior of the patient and smaller oral cavities which limit the examination. Good oral hygiene protocols should be applied during and after chemo-radio therapy motivating the children and parents or caregivers to maintain an appropriate level of oral hygiene to minimize the risk of developing decay, local infections, hemorrhage, and oral mucositis.